Day‐of‐the‐week effect and market liquidity: A comparative study from emerging stock markets of Asia†. (10th January 2021) - Khan, Badal; Aqil, Muhammad; Alam Kazmi, Syed Hasnain; Zaman, Syed Imran
Abstract: In the second half of the 20th century, it was observed that weekday‐of‐Monday generate significantly lower returns than other days of the week. Literature has shown that the day effect exists on weekdays of the week, which is different from this day Monday. This study investigates day‐of‐the‐week effect in returns and volume of stock in emerging Asian markets by using ordinary least square regression (OLS), generalized autoregressive conditional heteroscedasticity (GARCH) (1, 1) and Kruskal‐Wallis test. The data are obtained from Thomson Reuters from July 2013 to March 2019 for the market indices and volume. The OLS and GARCH (1, 1) are employed through Eviews, while Kruskal‐Wallis test is used through SPSS. The results show a significant day‐of‐the‐week effect in returns in China, South Korea, Taiwan, Thailand, Indonesia and Pakistan. On the other hand, no significant day‐of‐the‐week effect in returns is revealed in India and Malaysia. Furthermore, significant differences in traded volume on different days are also observed in all markets except for Malaysia, where Monday is the least traded day in most markets. No evidence for co‐occurrence of day‐of‐the‐week effect in returns and volume is observed. The findings affirm inconsistency in the day‐of‐the‐week effect.